2006
DOI: 10.1111/j.1399-6576.2006.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐dose dexmedetomidine or clonidine on the characteristics of bupivacaine spinal block

Abstract: Background: The purpose of this study was to compare the onset and duration of sensory and motor block, as well as the hemodynamic changes and level of sedation, following intrathecal bupivacaine supplemented with either dexmedetomidine or clonidine. Methods: In a prospective, double-blind study, 60 patients undergoing transurethral resection of prostate or bladder tumor under spinal anesthesia were randomly allocated to one of three groups. Group B received 12 mg of hyperbaric bupivacaine, group D received 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

54
514
9
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(582 citation statements)
references
References 37 publications
54
514
9
5
Order By: Relevance
“…[1][2][3] Also, it has been used safely as premedication or as a sedative agent in patients undergoing surgical procedures under regional anesthesia. 4,5 Although a synergistic interaction between intrathecal dexmedetomidine and local anesthetics has been observed in previous studies, [6][7][8][9] there are no clinical data regarding the effect of intravenous dexmedetomidine premedication on the duration of sensory and motor block during spinal anesthesia.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] Also, it has been used safely as premedication or as a sedative agent in patients undergoing surgical procedures under regional anesthesia. 4,5 Although a synergistic interaction between intrathecal dexmedetomidine and local anesthetics has been observed in previous studies, [6][7][8][9] there are no clinical data regarding the effect of intravenous dexmedetomidine premedication on the duration of sensory and motor block during spinal anesthesia.…”
Section: Introductionmentioning
confidence: 97%
“…16 OPS, sedation, and behavior scores in the recovery room were recorded by the same nurse at 60-min intervals. Once in the ward, only the OPS, and sedation scores were documented at 6,8,10,12,16,20, and 24 h post-operatively. Time to first analgesic dose (time between caudal injection and first administration of rescue analgesic), the total consumption of analgesic in the first 24 h and quality of sleep were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Intrathecal DEX was reported to produce analgesia in experimental animals, 9 prolong the duration of spinal bupivacaine 10 and potentiate the effect of spinal morphine in cancer pain in humans. 11 Few reports have described the use of epidural DEX in the management of acute post-operative pain in adults.…”
mentioning
confidence: 99%
“…Dexmedetomidine is still under evaluation as an ideal neuraxial adjuvant as it provides stable hemodynamic conditions, good quality of intraoperative and prolonged postoperative analgesia with minimal side effects [16][17][18]. Kanazi et al, demonstrated a significant prolongation in the duration of sensory and motor block with dexmedetomidine used as intrathecal additive for 0.5% heavy bupivacaine [16].…”
mentioning
confidence: 99%
“…Kanazi et al, demonstrated a significant prolongation in the duration of sensory and motor block with dexmedetomidine used as intrathecal additive for 0.5% heavy bupivacaine [16].…”
mentioning
confidence: 99%